2004
DOI: 10.1149/1.1637898
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chloride Implantation on Pit Initiation in Aluminum

Abstract: High-purity aluminum samples were implanted with 35 keV Cl ϩ then polarized in both Cl Ϫ -containing and Cl Ϫ -free electrolytes in order to ascertain corrosion behavior as a function of Cl Ϫ content in the oxide. Implant fluence between 5 ϫ 10 15 and 2 ϫ 10 16 Cl ϩ cm Ϫ2 resulted in little or no localized attack. Implant fluences of 3 ϫ 10 16 and 5 ϫ 10 16 Cl ϩ cm Ϫ2 resulted in significant pitting in a Cl Ϫ -free electrolyte with the severity scaling as a function of implant fluence. The low variability in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Pitting was not observed in the control cases (unimplanted and Ar-implanted) or in the low fluence implants (1 × 10 16 and 2 × 10 16 ions cm −2 ). Wall et al 94 suggested that these experiments demonstrated that a sufficient Cl − concentration in the oxide film or in the substrate metal would result in the nucleation of pits and that pit nucleation was independent of the solution composition as E pit measured in sulfate solutions were similar to those reported for Cl − containing solutions. The authors noted that pit initiation in the implanted electrodes due to the presence of Cl o in the underlying metal could not be discounted.…”
Section: Chloride In the Oxide: Ion Implantationmentioning
confidence: 75%
See 4 more Smart Citations
“…Pitting was not observed in the control cases (unimplanted and Ar-implanted) or in the low fluence implants (1 × 10 16 and 2 × 10 16 ions cm −2 ). Wall et al 94 suggested that these experiments demonstrated that a sufficient Cl − concentration in the oxide film or in the substrate metal would result in the nucleation of pits and that pit nucleation was independent of the solution composition as E pit measured in sulfate solutions were similar to those reported for Cl − containing solutions. The authors noted that pit initiation in the implanted electrodes due to the presence of Cl o in the underlying metal could not be discounted.…”
Section: Chloride In the Oxide: Ion Implantationmentioning
confidence: 75%
“…Wall et al 94 utilized ion implantation of a chlorine species, Cl + , into oxide covered Al to determine the effects of the ion-implanted chlorine on the pitting behavior and properties of the oxide film in Cl − free and Cl − containing electrolytes. The Al was 99.999% pure and test solutions were 50 mM KCl or K 2 SO 4 .…”
Section: Chloride In the Oxide: Ion Implantationmentioning
confidence: 99%
See 3 more Smart Citations